2021
DOI: 10.1186/s12958-021-00756-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Talin1 synergistically boosts β-estradiol-induced proliferation and pro-angiogenesis of eutopic and ectopic endometrial stromal cells in adenomyosis

Abstract: Adenomyosis (ADS) is an estrogen-dependent gynecological disease with unspecified etiopathogenesis. Local hyperestrogenism may serve a key role in contributing to the origin of ADS. Talin1 is mostly identified to be overexpressed and involved in the progression of numerous human carcinomas through mediating cell proliferation, adhesion and motility. Whether Talin1 exerts an oncogenic role in the pathogenesis of ADS and puts an extra impact on the efficacy of estrogen, no relevant data are available yet. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In another study, E2 treatment of endometrial stromal cells was demonstrated to be more angiogenic and associated with increased VEGFB protein expression. Meanwhile, these stimulants can be were partially eliminated by an estrogen-receptor antagonist (45). In the current study, miR-200s (except miR-200c) were shown to interact with LINC01541.…”
Section: Discussionmentioning
confidence: 53%
“…In another study, E2 treatment of endometrial stromal cells was demonstrated to be more angiogenic and associated with increased VEGFB protein expression. Meanwhile, these stimulants can be were partially eliminated by an estrogen-receptor antagonist (45). In the current study, miR-200s (except miR-200c) were shown to interact with LINC01541.…”
Section: Discussionmentioning
confidence: 53%
“…It has also been shown that angiogenesis participates in the pathophysiology of abnormal uterine bleeding and subfertility in AM [ 48 ]. Wang et al demonstrated that A-EuESCs treated with β-estradiol presented stronger pro-angiogenetic capacities, accompanied by the increased expression levels of VEGFB and ANGPTL4 proteins [ 14 ]. Furthermore, our chord plot analysis revealed that upregulated genes of FOXC2, TLR3, GATA6, HGF, IL-6, PTK2B, ANGPTL4 , and HIF1A were involved in the regulation of angiogenesis ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a heritable or acquired alteration in the eutopic endometrium may play an essential role in the occurrence of AM [ 9–12 ]. Eutopic endometrium of the women with AM showed abnormal biological processes, including decreased apoptosis [ 8 , 13 ], increased proliferation [ 10 ] and angiogenesis [ 14 ], and impaired cytokine expression and local production of estrogens, which involved the pathogenesis of AM by enhancing the infiltration of the endometrium to the junctional zone and the growth of ectopic tissue [ 15 ]. Numerous AM-based studies have concentrated on the eutopic endometrium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely known that estrogen exerts a proliferative effect on the endometrium, while adenomyosis has been repeatedly associated with endometrial cell overproliferation [ 28 ]. Indeed, a recent study demonstrated that supplementing culture of endometrial stromal cells from adenomyosis patients with estradiol (E2) significantly boosted their proliferation rates [ 29 ]. In addition to proliferation, estrogen has been shown to induce EMT in adenomyosis, a phenomenon frequently blamed for endometrial invasiveness [ 16 , 30 ].…”
Section: Role and Causes Of Hyperestrogenism In The Pathogenesis Of Adenomyosismentioning
confidence: 99%